Antimicrobial and pharmaceutical properties of the seed oil of leucaena leucocephala (Lam.) de wit (Leguminosae) (2011)
The seed oil of Leuconia leucocephala was investigated for its antimicrobial activity and the pharmaceutical properties of its lotion formulation determined. The oil was extracted from the pulverised dried seeds of the Leuconia leucocephala plant by cold maceration in n-hexane. The oil was tested against four bacteria (Staphylococcus aureus, Esherichia coli, Bacillus subtilis and Pseudomonas aeruginosa) and four fungi (Aspergilus niger, Rhizopus stolon, Penicillum notatum and Candida albicans) isolates. Gentamycin and tioconazole were the reference drugs respectively. The oil was later formulated as a lotion and the pharmaceutical properties of the formulation determined.The oil was found to have a concentration-dependent activity against both Gram-positive and Gram-negative bacteria, while showing no activity against the fungi tested. The lotion formulation of the oil containing oleic acid had good pharmaceutical properties and was stable over the test period. Leucaena leucocephala seed oil extract had a concentration-dependent activity against both Gram-positive and Gram-negative bacteria and the lotion formulation had good pharmaceutical properties.